FLUCTUATING JAUNDICE IN THE ADENOCARCINOMA OF THE AMPULLA OF VATER: a classic sign or an exception? - ALVES,José Roberto (2015)
Background Some authors consider the fluctuating jaundice as a classic sign of the adenocarcinoma of the ampulla of Vater. Objetive Assessing the frequency of fluctuating jaundice in their forms of its depiction in the patients with adenocarcinoma of the ampulla of Vater. Methods Observational and retrospective study, conducted through analyses of medical records from patients subjected to pancreatic cephalic resections between February 2008 and July 2013. The pathological examination of the surgical specimen was positive to adenocarcinoma of the ampulla of Vater. Concepts and differences on clinical and laboratory fluctuating jaundice were standardized. It was subdivided into type A and type B laboratory fluctuating jaundice. Results Twenty patients were selected. One of them always remained anicteric, 11 patients developed progressive jaundice, 2 of them developed clinical and laboratory fluctuating jaundice, 5 presented only laboratory fluctuating jaundice and one did not present significant variations on total serum bilirubin levels. Among the seven patients with fluctuating jaundice, two were classified as type A, one as type B and four were not classified due to lack information. Finally, progressive jaundice was the prevailing presentation form in these patients (11 cases). Conclusion This series of cases suggested that clinical fluctuating jaundice is a uncommon signal in adenocarcinoma of the ampulla of Vater.